Effect of Cilostazol on the P50 of the Oxygen-Hemoglobin Dissociation Curve - McKoy, Marshalyn; Allen, Kyomi; Richards, Andrea; Pepple, Dagogo (International Journal of Angiology, 2015)
Cilostazol is a drug used for the treatment of intermittent claudication caused by narrowing of the blood vessels and reduced oxygen supply, characterized by intense pain in the leg when walking. This study was designed to investigate the effect of cilostazol on the P50 of the oxygen hemoglobin dissociation curve. A total of eight healthy adult subjects were studied. Blood samples (0.5 mL) from each subject were mixed with 5, 10, and 20 μL of the 0.5 mg/mL stock solution of cilostazol to give concentrations of 10, 20, and 40 µg/mL equivalent to adult doses of 50, 100, and 200 mg, respectively. The control sample had no drug added. The oxygen hemoglobin dissociation curve of each sample was plotted and the P50 determined with a Hemox-Analyzer (TCS, Medical Products Division, Southampton, PA). The mean P50 for the control samples was 28.27 ± 0.43 mm Hg. The values of the samples exposed to 10, 20, and 40 µg/mL cilostozol were 29.63 ± 0.66, 30.15 ± 0.77, and 31.66 ± 0.62 mm Hg, respectively. There was a statistically significant difference (p < 0.01) between the control and samples exposed to 40 µg/mL cilostazol. This study suggests that cilostazol caused an increase in the release of oxygen from hemoglobin as shown in the P50 values. This effect was significant at the highest concentration of 40 µg/mL.
Keywords: cilostazol; oxygen hemoglobin dissociation curve; P50; oxygen release